1997
DOI: 10.1097/00006534-199704000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dose Aspirin on Thrombus Formation at Arterial and Venous Microanastomoses and on the Tissue Microcirculation

Abstract: In free flap/replantation surgery, failure is usually associated with thrombotic occlusion of a microvascular anastomosis (risk zone I) or, on occasion, flow impairment in the microcirculation of the transferred or replanted tissue (risk zone II). The objective of this study is to describe the effect of low dose aspirin on blood flow at both risk zones in microvascular surgery. Risk zone I: In rat femoral arteries and veins, thrombus formation was measured at the anastomoses using transillumination and videomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 45 publications
0
43
1
5
Order By: Relevance
“…Kort et al [40] observed that when administered 30 min prior to surgery aspirin had no antithrombotic effect, while other authors describe a significant increase in vessel patency when administered 10 h preoperatively [41]. Low-dose (5 mg/kg) aspirin has been shown to be sufficient to irreversibly block platelet thromboxane production while at the same time preserving endothelial prostaglandin I 2 and other antithrombotic prostaglandin synthesis [42]. …”
Section: Pharmacological Interventionmentioning
confidence: 99%
“…Kort et al [40] observed that when administered 30 min prior to surgery aspirin had no antithrombotic effect, while other authors describe a significant increase in vessel patency when administered 10 h preoperatively [41]. Low-dose (5 mg/kg) aspirin has been shown to be sufficient to irreversibly block platelet thromboxane production while at the same time preserving endothelial prostaglandin I 2 and other antithrombotic prostaglandin synthesis [42]. …”
Section: Pharmacological Interventionmentioning
confidence: 99%
“…However, the difference between experimental groups in capillary perfusion, measured as capillaries per visual field, proved that the inverting suture as a poor anastomosis technique caused a significant decrease in tissue perfusion over 24 h. This prolonged reduction in tissue perfusion was most likely due to microthrombosis secondary to dislodging of microemboli from the thrombogenic suture site, as was demonstrated in other studies. 3,8,15 We may conclude that in free-tissue transfer and any other case of smallvessel anastomosis, patency of the main vessels and blood flow is not a sufficiently predictive parameter for evaluation of peripheral tissue perfusion.…”
Section: Discussionmentioning
confidence: 97%
“…However, Peter emphasized that low dose aspirin (5mg/kg systemically) inhibits anastomotic venous thrombosis and improves microcirculatory perfusion in their rat model after provided quantitative data confirming and clarifying the beneficial effects of low dose [10].…”
Section: Discussionmentioning
confidence: 99%